2015
DOI: 10.1007/s10658-015-0681-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of qPCR assays for quantitative detection of Heterodera avenae and H. latipons

Abstract: Twelve Heterodera species are considered of major economic significance in cereals, of which Heterodera avenae, H. latipons and H. filipjevi are the most important. Precise identification and quantification of these nematodes are necessary to develop effective integrated pest control. This study reports on the use of the mitochondrial cytochrome oxidase subunit 1 (COI) gene to develop qPCR assays that could be used for the identification and quantification of H. avenae and H. latipons. Two qPCR primer sets, ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…The high specificity of the primer set was confirmed by the absence of amplicons of other Heterodera species ( H. schachtii , H. trifolii , and H. sojae ). This amplification efficiency could not be compared with previous studies because the primary factor was the number of nematodes instead of DNA concentration (Toumi et al, 2015). The sensitivity test showed that the detection limit of this primer set for H. glycines was 10 pg of DNA (Fig.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The high specificity of the primer set was confirmed by the absence of amplicons of other Heterodera species ( H. schachtii , H. trifolii , and H. sojae ). This amplification efficiency could not be compared with previous studies because the primary factor was the number of nematodes instead of DNA concentration (Toumi et al, 2015). The sensitivity test showed that the detection limit of this primer set for H. glycines was 10 pg of DNA (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…were used for the identification of H. glycines using a qPCR assay in 2009 in a study by Goto et al However, because the sibling species of H. glycines was found in a PCR-RFLP study based on the ITS rDNA region (Zheng et al, 2000), this ITS rDNA region could not be used for the identification of the nematode. For this reason, a qPCR assay based on the differences of another gene sequence was developed to discriminate between the Heterodera avenae group species ( H. avenae , H. filipjevi , and H. latipons ) by targeting the CO I gene (Toumi et al, 2013, 2015). Several studies have adopted the CO I gene for the DNA barcoding of the Heteroderidae family (Powers et al, 2018; Subbotin et al, 2018; Vovlas et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Using the biochemical and molecular approach, several new species were also described. Presently, developed molecular diagnostic tools, such as PCR-RFLP (Bekal et al, 1997;Subbotin et al, 1999Subbotin et al, , 2003Gäbler et al, 2000;Rivoal et al, 2003;Tanha Maafi et al, 2003;Abidou et al, 2005a;Ou et al, 2008;Fu et al, 2011), conventional PCR (Qi et al, 2012;Peng et al, 2013;Toumi et al, 2013a, b;Yan et al, 2013) and Real Time PCR (Toumi et al, 2015b) with specific primers, enable the differentiation of agriculturally important species both from their siblings and from less economically important species. In many of these techniques, the ITS rRNA gene was used as a marker for specific diagnostics.…”
mentioning
confidence: 99%